1999
DOI: 10.1002/(sici)1097-0223(199905)19:5<428::aid-pd563>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of βthalassaemia by reverse dot‐blot hybridization

Abstract: Thalassaemia is the most common genetic disease and is a public health problem of Thailand. Prevention and control of beta-thalassaemia diseases need accurate diagnosis of carriers and proper genetic counselling. Prenatal diagnosis is needed to prevent birth of the thalassaemic offspring in the couple at risk. This can be performed in the first trimester of pregnancy by DNA analysis using the polymerase chain reaction (PCR). Since there are more than 20 mutations causing beta-thalassaemia in Thailand, the poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The results showed that F.K. This was confirmed by reverse dot-blot hybridization of the PCR product with the oligonucleotide probe specific for the mutation (15). had the a-thal-1 (À À SEA ) and Hb CS genes ( Table 1).…”
Section: Reprintsmentioning
confidence: 65%
“…The results showed that F.K. This was confirmed by reverse dot-blot hybridization of the PCR product with the oligonucleotide probe specific for the mutation (15). had the a-thal-1 (À À SEA ) and Hb CS genes ( Table 1).…”
Section: Reprintsmentioning
confidence: 65%
“…The ␤-thalassemia mutations were characterized by polymerase chain reaction (PCR) and reverse dot-blot hybridization with the common allele-specific oligonucleotide (ASO) probes as previously described [14]. As it has been known that the frameshift mutation at codon 95 (+A) is also common among ␤-thalassemia patients in North Vietnam, the amplification refractory mutation system (ARMS) was used.…”
Section: Methodsmentioning
confidence: 99%
“…β‐Globin gene fragments were amplified using 5′ biotinylated oligonucleotide primers and hybridized to 17 membrane‐bound ASO probes for −31 (A‐G), −30 (T‐C), −28 (A‐G), codons 8/9 (+G), codon 15 (G‐A), codon 17 (A‐T), codon 19 (A‐G), codon 26 (G‐A), codons 27/28 (+C), IVS 1:1 (G‐T), IVS 1:5 (G‐C), codon 35 (C‐A), codon 41 (−C), codons 41/42 (−CTTT), codon 43 (G‐T), codons 71/72 (+A) and IVS 2:654 (C‐T) mutation as previously described (Winichagoon et al. , 1999).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of techniques based on polymerase chain reaction (PCR) amplification of DNA have been developed to identify globin gene mutations, such as dot‐blot hybridization, reverse dot‐blot hybridization (RDB), allele specific PCR (ARMS) and restriction enzyme analysis (Fucharoen et al. , 1995; Winichagoon et al. , 1999).…”
Section: Introductionmentioning
confidence: 99%